2017
DOI: 10.1007/s00395-017-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient activation of Akt upon reperfusion because of its novel modification by reduced PP2A-B55α contributes to enlargement of infarct size by chronic kidney disease

Abstract: Chronic kidney disease (CKD) increases myocardial infarct size by an unknown mechanism. Here we examined the hypothesis that impairment of protective PI3K-PDK1-Akt and/or mTORC-Akt signaling upon reperfusion contributes to CKD-induced enlargement of infarct size. CKD was induced in rats by 5/6 nephrectomy (SNx group) 4 weeks before myocardial infarction experiments, and sham-operated rats served as controls (Sham group). Infarct size as a percentage of area at risk after ischemia/reperfusion was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Activation of mitophagy blocked caspase-3 activation and attenuated reperfusion-mediated death in renal tubular epithelial cells. This finding is similar to that in previous reports demonstrating mitophagy is protective for the reperfused kidney [57, 58]. Therefore, this evidence firmly establishes the central role of mitochondria and the subsequent mitochondrial damage that amplifies the damage signal for the reperfused kidney.…”
Section: Discussionsupporting
confidence: 81%
“…Activation of mitophagy blocked caspase-3 activation and attenuated reperfusion-mediated death in renal tubular epithelial cells. This finding is similar to that in previous reports demonstrating mitophagy is protective for the reperfused kidney [57, 58]. Therefore, this evidence firmly establishes the central role of mitochondria and the subsequent mitochondrial damage that amplifies the damage signal for the reperfused kidney.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, our study demonstrated that the loss of PTEN expression in renal fibrosis, which has since been substantiated by many recent studies 14,18,41,42 . Both in vivo and in vitro, phosphorylation of AKT on Ser473 was increased as along with AA-induced kidney injury, which was consistent with previous studies 43 . In addition, we found impaired AKT activation with difference between Ser473 and Thr308 AKT phosphorylation during AKI-CKD transition, which also contributed to myocardial infarct size in 5/6 nephrectomy rats 43 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, PDK1 is also involved in many physiology and pathology changes, such as basilar artery smooth muscle cells proliferation 35 , autosomal dominant polycystic kidney disease 36 and insulin resistance 37 . In addition, the role PDK1 plays in chronic kidney disease is drawing more and more attention 38 . Although, there were few studies reported that PDK1 might regulate the apoptosis of podocytes in DN 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%